YiQi ChuTan Recipe Inhibits Epithelial Mesenchymal Transition of A549 Cells under Hypoxia - Chen, C-M; Sun, L-L; Fang, R-M; Lin, L-Z (Cellular and Molecular Biology, 2016)
This study aims to investigate mechanism of YiQi ChuTan Recipe (YCR) for inhibiting epithelial mesenchymal transition (EMT) of A549 cells under hypoxia. Flow cytometry was used to optimize YCR dosage by measuring A549 apoptosis, which were subjected to different treatments, including normal condition, hypoxia, hypoxia+YCR. Cell morphology and expression of EMT were measured with differential interference contrast microscopy, real-time PCR and western blot. Optimized condition of 4 mg/ml YCR and 2% O2 for 72 h was used to establish hypoxia. Under hypoxic condition, morphology of A549 cells changed from oblate fusi-form to elongated spindle. E-cadherin expression decreased while vimentin and fibronectin increased. EMT-related genes expression were significantly increased in hypoxia group compared to control group (P<0.05). After treatment with YCR, mesenchymal cells obviously decreased and EMT-related genes expression was significantly decreased (P<0.05). Changes of E-cadherin, vimentin and fibronection were significantly attenuated by YCR when compared to hypoxia group. Expression of proteins GRP78, SRC, MAPK, smad2/3 were significantly increased in hypoxia group compared to control group, but was significantly inhibited by YCR treatment. In conclusion, A549 cells underwent EMT under hypoxia while YCR reversed the EMT through GRP78, smad2/3 and SRC/MAPK signal pathway.